Genetic Variability and Haplotypes of Echinococcus equinus in a Donkey in Türkiye - Kilinc, Sg; Celik, F.; Kesik, Hk; Simsek, S. (Hellenic Veterinary Medical Soc, 2025)
Cystic echinococcosis (CE) is a parasitic zoonosis caused by Echinococcus granulosus sensu lato larva. This study was conducted for the molecular characterization of CE cysts obtained from a donkey naturally infected with CE cysts, and for the determination of haplotype diversity. Ten individual CE cysts localized in a donkey's liver were investigated. Genomic DNA was extracted from each individual cyst isolate. PCR product of 875 bp fragment the mitochondrial cytochrome c oxidase subunit 1 (mt-CO1) gene was amplified by using specific primers. The PCR products were purified and sequence analysis was performed. The partial sequences of the mt-CO1 gene belonging the CE cyst isolates were compared with published reference sequences. Partial sequences of mt-CO1 were identified as E. equinus. After haplotype analysis, two different haplotypes (Hap01 and Hap02) were identified. Nine sequences obtained from this study resided in the main haplotype (Hap01); however, another donkey sequence from this study was located in Hap02 with a nucleotide difference. Although Echinococcus granulosus s.s. (G1 and G3) is reported be the dominant species, and the current findings showed that E. equinus (G4) and its haplotypes could also circulate in donkeys from T & uuml;rkiye.
Keywords: Echinococcus equinus; Donkey; Haplotype; T & uuml;rkiy